Analysis of Ethanol to Reduce Solid Particle Pollution in SI Engines. (28th September 2021) - Sivaprakasam, P.; Maheandera Prabu, P.; Srinivasan, M.; Balakrishnan, S.; Karthikeyan, V. S.; Pon Selvan, M. Chithirai
Abstract : The present work carries out an experimental comparative analysis of the performance and emission of exhaust gases of the Otto cycle with four automotive times. The comparison was made between alternative fuels such as E10, E15, and E20, with both 90 and 95 octane each the commercialized fuel. The experimental tests were carried out with an engine load corresponding to 25% of the maximum load. After carrying out the tests, the following conclusions can be reached: on the performance and effective parameters of the engine, the obtained best indicator, and as expected, was the case E10 (90 octane). Also, the E15 (90 octane) showed a slight difference compared to the reference fuel E10 (90 octane). About emissions, it was found that these decrease as the concentration of ethanol in the fuel increases.